2003
DOI: 10.1093/deafed/eng018
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Psychosocial Adjustment of Deaf Students

Abstract: Deafness is more than a medical condition. Recent theories have emphasized the importance of environmental factors on the psychosocial development of deaf children. As part of a larger scale study, this article aims to investigate the impact of the following variables on deaf students' psychosocial adjustment in Turkey: student-related background and experiential characteristics, parent-related variables, school-related factors, and teacher-related variables. The sample of 1,097 deaf students enrolled in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 29 publications
3
66
2
3
Order By: Relevance
“…Although in contrast to the majority of previous research Polat, 2003;Van Eldik, 2005), our finding seems robust, as it remains even after controlling for a variety of possibly confounding factors. Moreover, the HH group differed significantly from the TH group, which did not exhibit the same gender pattern.…”
Section: Is There a Gender Difference?contrasting
confidence: 99%
See 1 more Smart Citation
“…Although in contrast to the majority of previous research Polat, 2003;Van Eldik, 2005), our finding seems robust, as it remains even after controlling for a variety of possibly confounding factors. Moreover, the HH group differed significantly from the TH group, which did not exhibit the same gender pattern.…”
Section: Is There a Gender Difference?contrasting
confidence: 99%
“…Though language problems tend to be more severe in children with profound hearing loss than in HH children (Fitzpatrick, Crawford, Ni, & Durieux-Smith, 2011), the association between degree of hearing loss and psychosocial problems is less clear. Whereas one study reports little relationship between degree of hearing loss and prevalence of diagnosable mental health problems ), another study suggests that higher degree of hearing loss predicted psychosocial adjustment problems in elementary, secondary, and high school students (Polat, 2003). To complicate further, HH children may even suffer more than those with profound hearing loss; in a study by , parents of 7-to 8-year-old children with milder hearing loss reported lower health-related quality of life for their children, as compared to parents of children with more severe losses.…”
Section: Psychosocial Problems In Hh Childrenmentioning
confidence: 95%
“…Kod djece kod koje je prisutna visoka razina ovladanosti znakovnim i govornim jezikom nije uočena veća učestalost psihosocijalnih poteškoća od one u njihovih čujućih vršnjaka (Sinkkonen, 1994;Polat, 2003). Djeca koja ne mogu uspješno komunicirati s okolinom, posebno s članovima obitelji i vršnjacima, četiri su puta više pogođena teškoćama u psihičkom zdravlju te su česte žrtve zlostavljanja.…”
Section: Kulturni Identitet I Psihičko Zdravljeunclassified
“…In the largest study to investigate this area, Polat (2003) investigated the impact of student background and experience, parent-related variables, school-related and teacher-related variables on the psychosocial adjustment of over 1,000 deaf children in Turkey. An observational scale for measuring social and emotional adjustment and self-image in deaf students (the Meadow/Kendall Social and Emotional Adjustment Inventory (SEAI) was administered by teachers and other educational professionals.…”
Section: Psychosocial Well-beingmentioning
confidence: 99%